Preparation Of Rajat Bhasma - Sanouriya, Jyoti; Prarthi, Preeti; Kashyap, C P; Thakur, Sudarshan Kumar (International Research Journal of Ayurveda & Yoga, 2020)
Bhasma means conversion of metal in such irreversible form that one cannot derive the original state (Apunarbhava) by the various pharmaceutical processes i.e. Shodhana, Jarana, Marana, Murchana, Amrutikarana etc. It is concept of reduction in particle size of metal and mineral upto micron or nano-particle size through Mardana process (herbal Sawrasa, Kwath, Jala, Gomutraor other DravDravya for Bhavna) and then exposed for certain quantum of heat as per Putamethod for managing certain diseases. Rajat Bhasma is an important one amongst the metallic Bhasma, prepared by using Aloevera pulp as levigating media. Rajat Bhasmais prepared by applying Laghupta by seven Puta. For each Puta2.5kg cow dung cake is used. After 4thPutaRajatBhasma fulfil the Ayurvedic parameter for test of prepared Bhasma. After this three Puta apply for increase the fineness of the Bhasma.